2021
DOI: 10.1101/2021.01.08.425901
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local Shifts in Inflammatory and Resolving Lipid Mediators in Response to Tendon Overuse

Abstract: Tendon inflammation has been implicated in both adaptive connective tissue remodeling and overuse-induced tendinopathy. Lipid mediators control the initiation and resolution of inflammation, but their roles within tendon are largely unknown. Here we profiled local shifts in intratendinous lipid mediators via liquid chromatography-tandem mass spectrometry in response to synergist ablation-induced plantaris tendon overuse. Sixty-four individual lipid mediators were detected in homogenates of habitually loaded pl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 97 publications
1
10
0
Order By: Relevance
“…It is appropriate to emphasize that these early fundamental studies are vital to understanding the pathogenesis of COVID-19 infections and the potential role of lipid mediators that could give useful new directions for treatments of COVID-19, long COVID and in lasting immunity. These new findings ( Table 1 ) and many other human studies for SPMs from international experts [ [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] ] would not have been possible without the i) complete stereochemical assignments of each of the potent bioactive SPMs produced by human and mouse leukocytes, ii) their biosynthesis from n-3 essential fatty acids (EPA and DHA) and iii) total organic synthesis with rigorous matching studies with endogenous SPMs along with our dedicated and talented organic chemistry collaborators summarized herein. In this relatively new SPM field, the Serhan lab has collaborated for many years with Professor Nicos Petasis and colleagues as part of the total synthesis core of our NIH-supported Program Project grant P01GM095467, Professor Trond Hansen and team in Oslo, Norway [ 56 ], Professor Bernd Spur and Anna Rodriguez [ [57] , [58] , [59] ], and the organic synthesis group at Cayman Chemical; for examples, see the custom synthesis of benzo-RvD1 analog mimetic [ 60 ] and the new RvE4 [ 61 ].…”
Section: Spms In Covid-19 Infections and Other Human Studiessupporting
confidence: 52%
See 2 more Smart Citations
“…It is appropriate to emphasize that these early fundamental studies are vital to understanding the pathogenesis of COVID-19 infections and the potential role of lipid mediators that could give useful new directions for treatments of COVID-19, long COVID and in lasting immunity. These new findings ( Table 1 ) and many other human studies for SPMs from international experts [ [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] ] would not have been possible without the i) complete stereochemical assignments of each of the potent bioactive SPMs produced by human and mouse leukocytes, ii) their biosynthesis from n-3 essential fatty acids (EPA and DHA) and iii) total organic synthesis with rigorous matching studies with endogenous SPMs along with our dedicated and talented organic chemistry collaborators summarized herein. In this relatively new SPM field, the Serhan lab has collaborated for many years with Professor Nicos Petasis and colleagues as part of the total synthesis core of our NIH-supported Program Project grant P01GM095467, Professor Trond Hansen and team in Oslo, Norway [ 56 ], Professor Bernd Spur and Anna Rodriguez [ [57] , [58] , [59] ], and the organic synthesis group at Cayman Chemical; for examples, see the custom synthesis of benzo-RvD1 analog mimetic [ 60 ] and the new RvE4 [ 61 ].…”
Section: Spms In Covid-19 Infections and Other Human Studiessupporting
confidence: 52%
“…Importantly, the many other elegant human studies on SPMs would not have been possible without reliance on the complete stereochemically defined synthetic SPMs and their internal standards for LC-MS-MS-based analyses with adult tissues [ [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] ] and adolescent human peripheral blood samples [ 38 ] as well as their scale-up for commercial availability [ 62 ]. A recent clinical trial reported that local topical treatment of gingival inflammation with a proresolving lipoxin/resolvin stable analog is safe and effective as well as activated endogenous production of SPMs present in peripheral blood [ 63 ].…”
Section: Spms In Covid-19 Infections and Other Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Innate immune system cells have a rapid, nonspecific response to microbes and injured cells. In fact, most innate immune system cells have PRR, which bind and recognise both PAMP present on microbes as well as DAMP (Kumar et al, 2011;Marshall et al, 2018). DAMPs, also known as alarmins, are nuclear, mitochondrial or cytosolic proteins released by cells upon infection, necrosis or injury (Roh and Sohn, 2018).…”
Section: Innate Immune System Cells In Tendinopathymentioning
confidence: 99%
“…DAMPs, also known as alarmins, are nuclear, mitochondrial or cytosolic proteins released by cells upon infection, necrosis or injury (Roh and Sohn, 2018). Once innate immune system cells bind proteins that trigger an immune response, they release a large number of cytokines, which in turn stimulate the blood flow to recruit more immune system cells to the site, thereby increasing inflammation (D'Addona et al, 2017;Marshall et al, 2018). Interestingly, tenocytes release pro-inflammatory cytokines upon injury, contributing to oedema and hyperaemia (D'Addona et al, 2017;Millar et al, 2017).…”
Section: Innate Immune System Cells In Tendinopathymentioning
confidence: 99%